The α5 neuronal nicotinic acetylcholine receptor subunits plays an important role in the sedative effects of ethanol but does not modulate consumption in mice - Santos, Nathan (2012)
BACKGROUND: Alcohol use disorders (AUDs) are a major public health problem, and the few treatment options available to those seeking treatment offer only modest success rates. There remains a need to identify novel targets for the treatment of AUDs. The neuronal nicotinic acetylcholine receptors (nAChRs) represent a potential therapeutic target in the brain, as recent human genetic studies have implicated gene variants in the α5 nAChR subunit as high risk factors for developing alcohol dependence. METHODS: Here, we evaluate the role of α5* nAChR for ethanol-mediated behaviors using male α5+/+ and α5−/− mice. We characterized the effect of hypnotic doses of ethanol and investigated drinking behavior using an adapted Drinking-in-the Dark (DID) paradigm that has been shown to induce high ethanol consumption in mice. RESULTS: We found the α5 subunit to be critical in mediating the sedative effects of ethanol. The α5−/− mice showed slower recovery from ethanol-induced sleep, as measured by loss of righting reflex. Additionally the α5−/− mice showed enhanced impairment to ethanol-induced ataxia. We found the initial sensitivity to ethanol and ethanol metabolism to be similar in both α5+/+ and α5−/− mice. Hence the enhanced sedation is likely due to a difference in the acute tolerance of ethanol in α5−/− mice. However the α5 subunit did not play a role in ethanol consumption for ethanol concentrations ranging from 5% to 30% using the DID paradigm. Additionally, varenicline was effective in reducing ethanol intake in α5−/− mice. CONCLUSION: Together, our data suggest that the α5 nAChR subunit is important for the sedative effects of ethanol but does not play a role in ethanol consumption in male mice. Varenicline can be a treatment option even when there is loss of function of the α5 nAChR subunit.